The Effectiveness of Health Education Using Si NaNing Module to Increase Independence in Stunting Prevention - Rahmadona Rahmadona; Aura Bella Gizta; Tiyara Safitri; Haryadi Haryadi; Nining Sulistyowati; Fidyah Aminin (JURNAL KEBIDANAN, 2023)
One of the public health problems that occur in infants and toddlers on Indonesia is stunting. The prevalence of stunting in the Riau Island Province SSGI data for 2021 shows an increase in the prevalence of stunting from 7.21% to 17.6%. One of the efforts to prevent stunting is to overcome anemia. The prevalence rate of anemia is still high due to the low level of adherence of pregnant women in taking iron supplements. This study aimed for accurate, precise, and up-to-date information to prevent anemia and stunting. The purpose of this study was to determine the effect of Si NaNing Module on the independence of pregnant women in preventing anemia and a quasi-experimental conducted in Tanjungpinaa ng City from May to October 2022. The research design was a quasi-experimental design with a pre-posttest with control group design. The instrument used is a questionnaire. The population in this study were all pregnant women in Tanjungpinang City. The sample in this study were 100 experimental respondents and 100 control respondents. Data analysis used the T test. The results showed that there was an effect of the module on responsibility (p-value 0.001), autonomy (p-value 0.001), initiative (p-value 0.001), and self-control (p- value 0.001) on anemia prevention and stunting. Thus, the Si NaNing Module can be used as an effort to increase mother's independence in preventing anemia and stunting.